Pelatihan Update Data Simpan Pinjam KPNRI Welas Asih Banjarbaru - Mukhlis, Iwan Fitriady; Salim, Yeffriansjah; Tjitradi, Darmansyah; Eliatun, Eliatun; Herliani, Erna (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
A co-operation of state officials of the welfare established in 1974 under the auspices of teachers of the Basic School of Banjar district on Ahmad Yani Street Km 33,3 no.39 town Banjarbaru. At the end of 2022, 1,000 active members were registered and were spread evenly in 4 districts: the landscape, the coral, the cempaka and the martapura. The lending data storage application has been running since 2001 until now the update of the loan storage data in 2023 is focused on accelerating the process of payment of member loan bills, which at the time of bill payment is only filled with the members of KPNRI who wait only so that the input of payment data is very fast and efficient considering the number of members who perform lending activity more than 600 transactions / records per month. Other loan storage data update is the process of updating the transfer of KPNRI member homebase so that the billing process can be done in accordance with the location of the latest member home base, as well as updating data maintenance and repair of database table files if there are errors due to power failure. Results P2M training participants are able to operate the application with input member loan data, payment member loan bills as well as printing bills on all work units with correct information.